Optimization of Revealing Online Fraud Crimes by the Other-Type of Crime Unit to Realize Justice Transparency in the Jurisdiction of Sragen Police Station - Asmanandaini, Sri (Advances in Police Science Research Journal, 2024)
Online fraud is a problem that often occurs in the jurisdiction of the Sragen Police. The lack of public education, technological advances, and the difficulty of revealing it has made people more in favor to commit online fraud. The total report of complaints to the Sragen Police Station regarding criminal acts of online fraud is so many, but the efforts to reveal them were still zero. This study was undertaken to identify the problems related to efforts to reveal criminal acts of online fraud by the Other-Type of Crime Unit in the jurisdiction of the Sragen Police Station. The research was conducted by using a qualitative approach by combining both field research and descriptive analysis methods. Concerning the theory that the writer uses to assist the analyzing research are Organizational Resources theory, POAC theory, and SWOT theory. The writer also used the concept of optimazation, concept of revealing criminal acts, the concept of online fraud, and the concept of justice transparency. This research was conducted by the writer in the jurisdiction of the Sragen Police. From the results of the research, it shows that the main obstacle in revealing online fraud is the difficulty in tracking the perpetrators, both identity and their location. This is influenced by several factors, both internal and external from the Sragen Police Satuan Reskrim Crime Unit. Therefore the writer suggests empowering the personnel, finances supports as well as facilities and advanced technology infrastructures from the Police, increasing cooperation both from within the Police and with other agencies to help optimize the disclosure of online fraud crimes at the Sragen Police by the Tipidter Unit.